(untitled) (International Journal of Smart Agriculture, 2025)
The enhanced consequences of climate change increase the need for effective sustainability efforts. Protected agriculture, comprising greenhouses, net houses, and vertical farms, provides a good answer as it offers controlled buffers against climatic extremes that threaten crops. The use of smart technologies like IoT monitoring, AI, automation, blockchain and precision farming has advanced the possibilities of these systems. All of these work together to allow monitoring and real-time decision making, optimize resource usage, boost productivity, increase transparency and traceability within the supply chain. Some of the barriers that hinder change are the high costs, lack of technical skills, and limited infrastructure. This paper aims to systematically analyzes recent developments in protected agriculture and autonomous farming systems considering barriers to implementation and explore avenues such as innovative low-cost smart devices, renewable powered systems, and non-adaptive resilient crops integrated with sustainability focused climate policies. By highlighting these innovations, this paper will motivate policymakers, researchers, and practitioners towards devising climate-resilient food systems.